2020
DOI: 10.2185/jrm.2020-004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of glecaprevir and pibrentasvir combination therapy in old-aged patients with chronic hepatitis C virus infection

Abstract: Objective: Combination therapy with glecaprevir and pibrentasvir (G/P) has been shown to provide a sustained virologic response (SVR) rate of >97% in patients with chronic hepatitis C virus (HCV) infection in the first published real-world Japanese data. However, a recently published study showed that the treatment was often discontinued in patients ≥75 years old, resulting in low SVR in intention-to-treat (ITT) analysis. Thus, our aim was to evaluate real-world data for G/P therapy in patients ≥75 years of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The SVR12 rate in our real-world data was slightly higher in comparison to those in a phase III Japanese study 9 and in the ASTRAL-4 study. 5 In addition, the SVR12 rate in the present study was comparable to the rates in our previous studies 14,15 and other studies [16][17][18] using other DAA treatment regimens for patients with chronic hepatitis or compensated cirrhosis. One of the reasons for the high SVR rate in the present study was the absence of virologic failure in patients who completed 12 weeks of treatment.…”
Section: Discussionsupporting
confidence: 88%
“…The SVR12 rate in our real-world data was slightly higher in comparison to those in a phase III Japanese study 9 and in the ASTRAL-4 study. 5 In addition, the SVR12 rate in the present study was comparable to the rates in our previous studies 14,15 and other studies [16][17][18] using other DAA treatment regimens for patients with chronic hepatitis or compensated cirrhosis. One of the reasons for the high SVR rate in the present study was the absence of virologic failure in patients who completed 12 weeks of treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Among the risk factors identified as significant from univariate analyses, age and TB remained as independent factors after multivariate analysis. Some Japanese real-world cohorts with median ages around 65 years old revealed that the incidence of GP-induced hyperbilirubinemia was within the range of 0.6–2% [ 23 , 24 , 25 , 26 , 27 , 28 ]. However, Tamori et al indicated in their real-world cohort that the median age of patients with hyperbilirubinemia was high, at 70 years old [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Watanabe and colleagues analysed a cohort ( n = 59) of patients aged >75 years or older undergoing G/P, showing overall SVR12 rates of 98.3% and 100%, in the ITT and PP analyses respectively 10 . Moreover, they compared the SVR12 rates between patients >75 years of age and those <75 years of age finding similar SVR rates, even after stratification for liver status, prior DAA treatment, duration of treatment, gender, history of HCC and FIB4 index >3.25 10 . The recent analysis of another Japanese cohort by Komaki and colleagues showed similar results with SVR12 rates of 95.8% and 98.6% in the ITT and PP analysis, respectively, in a group of patients aged over 75 undergoing treatment with G/P for 8 or 12 weeks 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The combination of G/P includes a protease inhibitor, a drug class which is contraindicated in patients with decompensated disease, has more DDIs than other DAA classes and is perceived by most clinicians as being slightly more difficult to manage in fragile/complex patients 9 . For this reason, the efficacy and safety of G/P in elderly patients have been reported in relatively small studies coming mostly from referral centres in Asia 10–12 . A recent real‐life study from Italy in HCV patients >80 years of age found that G/P achieved SVR rates of 100% with no significant side effects; however, G/P was given only to 25% of the total cohort of patients, with most patients receiving SOF‐based regimens 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation